The ABCs of Writing Motivation and Supportive Writing Environment: A Case Study of Islamic Education Students - Siti Aishah, Chu Abdullah; Mohd Nizam, Sahad; Mohd Sham, Kamis; Mary Fatimah, Subet (Iquz Galaxy Publisher, 2026)
The present study explores writing motivation among Islamic Education students by integrating the ABCs of Writing Motivation framework with a supportive writing environment (SWE) model. Using a qualitative design with descriptive content analysis, interviews were conducted with 11 undergraduate students from Universiti Malaysia Sarawak, and the data were analyzed thematically using QSR NVivo. The findings show that Feedback, Beliefs, and Instructors were the most influential motivational factors, shaping students’ confidence and their willingness to engage consistently in writing activities. Goals and Appeal also played meaningful roles, particularly in relation to students’ faith-based values, moral purpose, and their desire to contribute to Islamic knowledge. Many participants perceived writing not merely as an academic task but as a spiritual act that supports da’wah, deep reflection, and ongoing personal development. Components of SWE, including constructive feedback, appropriate use of technology, and clear lecturer guidance, further enhanced students’ motivation, clarity of expression, and sense of achievement. These elements worked together to create a positive atmosphere that encouraged students to write more confidently and purposefully. Overall, the study highlights the importance of combining internal motivational drivers with supportive environmental structures to promote academic excellence, spiritual growth, and lifelong learning, offering practical implications for educators and curriculum planners in Islamic Education.